"Vegetable, Fruit and Cereal" Dietary Pattern in Chinese Children Aged 3–12 Years Old: Is It Associated with Dietary Protein and Micronutrient Inadequacy? (P18-104-19). (13th June 2019) - Meng, Liping; Wang, Yan; Li, Ting; Szeto, Ignatius Man-Yau
Abstract: Objectives: To identify the dietary pattern and to investigate the association between dietary pattern with dietary protein and micronutrient inadequacy among Chinese children, using a national representative data. Methods: A total of 1484 children aged 3–12 years from the 2011 China Health and Nutrition Survey (CHNS) were included for analysis. Dietary nutrients intake were assessed based on three 24-h recall periods. Overall micronutrient inadequacy (OMI) was defined as having a mean adequacy ratio (MAR) below 0.75, where MAR was calculated as the sum of each nutrient adequacy ratio divided by the number of involved nutrients. Nutrient inadequacy was defined as the proportion of individuals whose nutrient intake was less than the estimated average requirement. Dietary patterns were derived using factor analysis with a principal component method. The logistic regression model was employed to explore the association of nutrient inadequacy with tertile categories of standardized dietary pattern score. Results: A "vegetable, fruit and cereal" (VFC) dietary pattern, characterized by high consumption of vegetables, fruits and cereals, was identified. With VFC dietary pattern score increasing, the prevalence of inadequacy of protein, vitamin A, thiamine, riboflavin, vitamin C, niacin, calcium, iron, zinc, selenium, phosphorus, magnesium and OMI was decreasing ( P < 0.01). After adjustment confounders of age, gender, urbanization level and daily energy intake, the VFC pattern was significantly negatively associated with involved dietary nutrient inadequacy except calcium, with the odds ratio (OR) ranging from 0.10 to 0.36 for the medium tertile and 0.02 to 0.18 for the upper tertile, with the lower tertile as the reference group. Conclusions: This study indicates that a "vegetable, fruit and cereal" dietary pattern are negatively associated with inadequacy of protein and micronutrients in Chinese children. Funding Sources: This research received no external funding. The datasets we used are based on the online resources, which are open to the public for free. Supporting Tables, Images and/or Graphs: